Spiral Orbit

A particle moves in two dimensions under the influence of a central force determined by the potential V ( r ) = α r p + β r q V(r) =\alpha r^p+\beta r^q . Find the powers of p p and q q which make it possible to achieve a spiral orbit of the form r = c θ 2 r=c\theta^{2} , with c c a constant. - Determine the value of p q \frac{p}{q}
Details and Assumptions
1) p > q |p|>|q|


The answer is 1.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Karan Chatrath
Apr 8, 2020

Consider a point in space parameterised in polar coordinates:

x = r cos θ x = r\cos{\theta} y = r sin θ y = r\sin{\theta}

x ˙ = r ˙ cos θ r θ ˙ sin θ \dot{x} = \dot{r}\cos{\theta} - r\dot{\theta}\sin{\theta} y ˙ = r ˙ sin θ + r θ ˙ cos θ \dot{y} = \dot{r}\sin{\theta} + r\dot{\theta}\cos{\theta}

Assuming the particle mass to be unity, the kinetic energy of the system is:

T = 1 2 ( x ˙ 2 + y ˙ 2 ) = 1 2 ( r ˙ 2 + r 2 θ ˙ 2 ) T = \frac{1}{2}\left(\dot{x}^2 + \dot{y}^2\right) = \frac{1}{2}\left(\dot{r}^2 + r^2 \dot{\theta}^2\right) V = A r p + B r q V = Ar^p + Br^q

Applying Lagrangeé equation in terms of the θ \theta coordinate gives:

d d t ( T θ ˙ ) T θ + V θ = 0 \frac{d}{dt}\left(\frac{\partial T}{\partial \dot{\theta}}\right) - \frac{\partial T}{\partial \theta} + \frac{\partial V}{\partial \theta}=0 d d t ( r 2 θ ˙ ) = 0 \implies \frac{d}{dt}\left(r^2 \dot{\theta}\right) = 0 r 2 θ ˙ = K ( 1 ) \implies r^2\dot{\theta} = K \ \dots \ (1)

Where K K is some constant.

Now, applying the energy conservation principle gives: T + V = K 1 T + V = K_1

1 2 ( r ˙ 2 + r 2 θ ˙ 2 ) + A r p + B r q = K 1 \implies \frac{1}{2}\left(\dot{r}^2 + r^2 \dot{\theta}^2\right) + Ar^p + Br^q = K_1

Here, K 1 K_1 is also constant.

Re-arranging the above gives:

r ˙ 2 = K 1 A r p B r q r 2 θ ˙ 2 \dot{r}^2 = K_1 - Ar^p - Br^q - r^2 \dot{\theta}^2

Consider the right-hand side of the above equation. Using (1), we get:

R H S = K 1 A r p B r q r 2 θ ˙ 2 = K 1 A r p B r q K 2 r 2 \mathrm{RHS} = K_1 - Ar^p - Br^q - r^2 \dot{\theta}^2=K_1 - Ar^p - Br^q - \frac{K^2}{r^2}

Now consider the left-hand side:

We have:

r = c θ 2 r = c\theta^2 θ = K 3 r \implies \theta = K_3 \sqrt{r} r ˙ = 2 c θ θ ˙ \dot{r}=2c\theta\dot{\theta}

Using (1) in the equation above gives:

r ˙ 2 = K 4 1 r 3 \dot{r}^2 = K_4 \frac{1}{r^3}

L H S = r ˙ 2 = K 4 1 r 3 \mathrm{LHS} = \dot{r}^2 = K_4 \frac{1}{r^3}

Now, for LHS to be equal to RHS, K 1 K_1 must be zero and q = 2 q=-2 and B = K 2 B=-K^2 and p = 3 p = -3 and K 4 = A K_4 =-A

Essentially p > q \lvert p \rvert > \lvert q \rvert

And the answer is 1.5 \boxed{1.5} .

I do not know if this is the correct approach because assuming that the total energy is zero to satisfy the condition does not seem very natural to me.

@Mark Hennings I would like to know your take on this approach.

Karan Chatrath - 1 year, 2 months ago

A simpler way to think of this is to use conservation of energy (there is a potential, so the force is conservative). Thus E = 1 2 m ( r ˙ 2 + r 2 θ ˙ 2 ) + V ( r ) E = \tfrac12m(\dot{r}^2 + r^2\dot{\theta}^2) + V(r) is constant, and (since the force is central) angular momentum is conserved, so r 2 θ ˙ = h r^2\dot{\theta} = h is constant. To have a trajectory r = c θ 2 r = c\theta^2 we have r ˙ = 2 c θ θ ˙ = 2 c h θ r 2 r ˙ 2 = 4 c h 2 r 3 \dot{r} = 2c\theta\dot{\theta} = \frac{2ch\theta}{r^2} \hspace{2cm} \dot{r}^2 \; = \; 4ch^2 r^{-3} so that E = 2 m c h 2 r 3 + 1 2 m h 2 r 2 + α r p + β r q E \; = \; 2mch^2r^{-3} + \tfrac12mh^2r^{-2} + \alpha r^p + \beta r^q The only way this can be constant is when E = 0 E=0 , and p , q = 2 , 3 p,q =-2,-3 in some order, with specific values of α , β \alpha,\beta . This is clearly a very special case!

Mark Hennings - 1 year, 2 months ago

Log in to reply

Thank you for the insights

Karan Chatrath - 1 year, 2 months ago

Since the force is central, r 2 θ ˙ = r^2\dot {\theta}= constant. From the equation of the path, r r is proportional to θ 2 r ˙ \theta^2\implies \dot {r} is proportional to r 1.5 r^{-1.5} . So r ¨ \ddot {r} is proportional to r 4 r^{-4} . Since the potential is α r p + β r q αr^p+βr^q , the acceleration, which is purely radial, is proportional to ( α p r p 1 + β q r q 1 ) -(αpr^{p-1}+βqr^{q-1}) . Therefore r ¨ r θ ˙ 2 \ddot {r}-r\dot {\theta}^2 , which is of the form a r 4 + b r 3 \dfrac{a}{r^4}+\dfrac{b}{r^3} , is identical with ( α p r p 1 + β q r q 1 ) -(αpr^{p-1}+βqr^{q-1}) . So, p 1 = 4 , q 1 = 3 p = 3 , q = 2 p q = 3 2 = 1.5 p-1=-4, q-1=-3\implies p=-3, q=-2\implies \dfrac{p}{q}=\dfrac{3}{2}=\boxed {1.5}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...